2018
DOI: 10.1186/s10195-018-0509-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and clinical strength assessment after infraspinatus-sparing surgical approach to scapular fracture: Does it really make a difference?

Abstract: BackgroundSurgical treatment of scapular fractures with posterior approach is frequently associated with postoperative infraspinatus hypotrophy and weakness. The aim of this retrospective study is to compare infraspinatus strength and functional outcomes in patients treated with the classic Judet versus modified Judet approach for scapular fracture.Patients and methods20 cases with scapular neck and body fracture treated with posterior approach for lateral border plate fixation were reviewed. In 11 of 20 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
9
0
2
Order By: Relevance
“…First of all, the number of included patients. Incidence of scapula body fractures is rather low, thus since the scapular body Fx is considered rare, the number of 21 enrolled patients can be regarded as adequate and similar compared to previous published studies focusing on scapula body Fx [15,34,36,37].…”
Section: Limitationssupporting
confidence: 62%
“…First of all, the number of included patients. Incidence of scapula body fractures is rather low, thus since the scapular body Fx is considered rare, the number of 21 enrolled patients can be regarded as adequate and similar compared to previous published studies focusing on scapula body Fx [15,34,36,37].…”
Section: Limitationssupporting
confidence: 62%
“…Most scapular fractures can be adequately managed through less aggressive, limited approaches. 11,20,22,23 However, because of the need for a scapular osteotomy, removal of a newly formed bone, and rib fixation, we performed an extensive Judet approach, as suggested for surgery in delayed cases. 7,8 Dual plating of both medial and lateral scapular borders was performed.…”
Section: Discussionmentioning
confidence: 99%
“…A DASH score between 0 and 29 is considered to be the point where the patient no longer considers their upper limb disorder is a problem (20). Past studies reported mean DASH score between 8.1 and 14 for all patients who underwent surgical interventions for scapular neck and body fractures (10,13,16,18,19,21). The patient-reported functional outcome using SF-36 questionnaire scored between 70 and 89.6 (comparable to normal healthy population 61 to 84), with exception to two subcategories, i.e., REE (role limitations due to emotional problems) and REP (role limitations due to physical health).…”
Section: Discussionmentioning
confidence: 99%
“…We believe it is essential to restore the anatomy of the scapular blade to prevent scapulothoracic joint disorder such as snapping scapular syndrome resulting from the abnormal articulation of the scapulothoracic joint (15). The Modified Judet approach allows similar access to essential landmarks for fracture reduction and fixation with lesser soft tissue stripping, particularly the infraspinatus muscle and its blood supply (9,16). A drain was left under the infraspinatus muscle before closing the skin.…”
Section: Surgical Approachmentioning
confidence: 99%